Regenerate lake in Taman Gelora using enviromently responsible design at Kuantan Pahang - Harun, Nur Ain (2018)
This project proposal deals with the regenerating of the lake at part of Taman Gelora. The aim of the project is to regenerate lake in Taman Gelora from ecological collapse to habitat oasis. The project proposal explores what impact the restoration of this park to become more safety with protects the natural sensitive area through environmentally responsible design at Taman Gelora Kuantan. By analyzing part of Taman Gelora as a natural sensitive area, there are three main challenges such as poor an environmental impact as an ecological collapse of habitat, lack of connectivity with interesting activity in existing area and a park which has become promote an ecological design approach. Other than that, lack of proper community spaces and green spaces for the user are socialized and interact with each other. As a solution to these challenges, put forward a vision and a strategy for Taman Gelora, with the lake as a point of an interest. The strategy focuses on promoting human and nature. The lakes area becomes the structure that ties these themes together. Promoting the human activity in connection with the lake area as the main attraction to this park to protect the biodiversity and promote human interaction with water. In continuation of the vision, site visit has done, showing in detail plans and visualizations. Imagine a park on 28 acres of the whole area of Taman Gelora. Initially, the Taman Gelora proposal suggests ways to regenerate what is currently an environmental impact in the natural sensitive area into an interesting green space that reconnects the people towards the lake and promoting new attraction with good scenic quality. The project was also intended as a typical landscape design approach to restoring environmental perspective to create an ecological design approach that promotes a sense of welcoming to this area. Other than that, provide a natural environment to promoting as an environmental sustainability and ecologies